EFEKTIFITAS PENGGUNAAN LEAFLET, WHATSAPP REMINDER TERHADAP KONSUMSI TABLET TAMBAH DARAH (TTD) DAN PENINGKATAN HEMOGLOBIN PADA KEHAMILAN - Miratu Megasari; Risa Pitriani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The prevalence of pregnancy anemia in Indonesia remains high, primarily driven by iron deficiency. At PMB Dince Syafrina within the Rumbai Public Health Center working area, an average of 62.5% out of 40 pregnant women visiting monthly suffer from anemia. Adherence to iron supplementation is a key factor in preventing anemia, highlighting the need for effective information media such as leaflets and WhatsApp reminders.To improve adherence to iron supplementation and increase hemoglobin (Hb) levels in third-trimester pregnant women.This study utilized a quasi-experimental approach with a randomized pretest-posttest group design, comparing two groups of third-trimester pregnant women. The control group received education via leaflets, while the intervention group received education via leaflets accompanied by WhatsApp reminders. Each group was provided with 30 iron tablets. Adherence was monitored for one month, and Hb levels were measured before and after the intervention. Data were analyzed bivariately using the parametric paired t-test and the non-parametric Wilcoxon test.The WhatsApp reminder group demonstrated a significantly higher adherence rate (86.7%) compared to the leaflet group (46.7%) with a -value of 0.021. Furthermore, the average increase in hemoglobin levels in the WhatsApp reminder group ( ) was also significantly greater than that in the leaflet group ( ) with a -value of 0.001. Integrating WhatsApp reminders into antenatal care services is proven to be more effective in increasing iron supplementation adherence and hemoglobin levels among third-trimester pregnant women, making it a practical, effective, and sustainable health promotion strategy.Keywords: Pregnancy anemia, Compliance, Iron supplementation, WhatsApp reminder, Leaflet